Enhancing Vocational Education Through Collaborative Learning: A Pathway to Innovation and Industry Readiness - Firta Panjaitan Panjaitan; Roma Sinta; Juliana Batubara (Journal of Education Innovation and Curriculum Development, 2024)
This research explores the role and impact of collaborative learning as an innovative approach in vocational education, aiming to address the growing demand for both technical proficiency and soft skills in the modern workforce. The study investigates how collaborative learning strategies enhance student engagement, foster deeper understanding, and improve real-world problem-solving capabilities, ultimately contributing to better industry-readiness. A qualitative-descriptive methodology was employed, incorporating literature analysis, classroom observations, and interviews with vocational educators and students. The findings reveal that collaborative learning not only improves academic outcomes but also strengthens essential competencies such as communication, teamwork, and adaptability. Additionally, it encourages vocational teachers to adopt more interactive and student-centered pedagogical methods. However, the research also identifies several barriers to effective implementation, including limited teacher training, infrastructure constraints, and rigid curricula. The study concludes that successful integration of collaborative learning requires institutional support, targeted teacher development, and supportive policy frameworks. By overcoming these challenges, vocational education systems can better prepare learners for dynamic, team-oriented professional environments. This research contributes valuable insights for educators, institutions, and policymakers seeking to enhance the quality and relevance of vocational training through pedagogical innovation.